Nucleotide depletion reveals the impaired ribosome biogenesis checkpoint as a barrier against DNA damage. (2nd June 2020) - Pelletier, Joffrey; Riaño‐Canalias, Ferran; Almacellas, Eugènia; Mauvezin, Caroline; Samino, Sara; Feu, Sonia; Menoyo, Sandra; Domostegui, Ana; Garcia‐Cajide, Marta; Salazar, Ramon; Cortés, Constanza; Marcos, Ricard; et al.
Abstract: Many oncogenes enhance nucleotide usage to increase ribosome content, DNA replication, and cell proliferation, but in parallel trigger p53 activation. Both the impaired ribosome biogenesis checkpoint (IRBC) and the DNA damage response (DDR) have been implicated in p53 activation following nucleotide depletion. However, it is difficult to reconcile the two checkpoints operating together, as the IRBC induces p21‐mediated G1 arrest, whereas the DDR requires that cells enter S phase. Gradual inhibition of inosine monophosphate dehydrogenase (IMPDH), an enzyme required for de novo GMP synthesis, reveals a hierarchical organization of these two checkpoints. We find that the IRBC is the primary nucleotide sensor, but increased IMPDH inhibition leads to p21 degradation, compromising IRBC‐mediated G1 arrest and allowing S phase entry and DDR activation. Disruption of the IRBC alone is sufficient to elicit the DDR, which is strongly enhanced by IMPDH inhibition, suggesting that the IRBC acts as a barrier against genomic instability. Synopsis: How S‐phase DNA damage responses and G1 arrest via the impaired ribosome synthesis checkpoint (IRBC) cooperate in p53 activation upon nucleotide depletion has remained unclear. Different levels of inosine monophosphate dehydrogenase (IMPDH) inhibition now reveal a hierarchical organization of these two genomic instability barriers. Gradual inhibition of GMP synthesis by IMPDH inhibitors elicits primarily the IRBC, and secondarily ATR/Chk1 activation. Enhanced proteasomal p21 degradation upon severe nucleotide depletion overcomes IRBC‐dependent G1 arrest, leading to replicative stress. Cells exposed to prolonged IMPDH inhibition and replicative stress experience DNA damage. IRBC disruption alone can elicit DNA damage, which is strongly enhanced by IMPDH inhibition. Abstract : Hierarchical organization of p21‐mediated G1 arrest and S‐phase DNA damage response signaling ensures genomic stability upon increasing inhibition of nucleotide synthesis enzyme IMPDH.